SPREAD OF HELICOBACTER PYLORI - INFECTION AMONG ADOLESCENTS AND OPPORTUNITIES TO INCREASE EFFICACY OF ITS TREATMENT - A.M. Vavilov; V.P. Vavilova; N.A. Il'ina; I.A. Nechaeva ("Paediatrician" Publishers LLC, 2007)
The article highlights the data on the spread of Helicobacter pylori (НР) infection among adolescents aged 15-17, its associations with the pathology of the gastroduodenal zone and eradication therapy efficacy. They showed that НР-infection was disc closed among 70% of adolescents, residing in a large industrial city and in 99% of cases it was accompanied by the clinical symptoms of stomach and duodenum lesions. Adolescents without heliconbacteriosis of the gastro duodenal zone showed symptoms of the given diseases only in 16.4% of cases. НР associated and НР cnonassociated changes in the stomach and duodenum mucous tunic among the examined patients were reversible. Successful eradication of H. pylori along with the first line therapy was achieved among 50-60% of adolescents. Introduction of the mixture of bacteria lysates to the treatment was accompanied by the eradication of H. pylori among 95% of the examined patients. Thus, the application of the above said mixture in addition to the commonly accepted scheme of treatment for НР associated diseases of the gastro duodenal zone increases its efficacy, which allows the authors to recommend the immunomodulator for the combined therapy of НР-infection.Key Words: Adolescents, Helicobacter Pylori, Treatment, Mixture of Bacteria Lysates.